Metode Pengelolaan Kebun Raya Melalui Pendekatan Corporate Social Responsibility dalam Upaya Penerapan Pariwisata Berbasis Tri Hita Karana - Meizar Rusli (Journal of Tourism Destination and Attraction, 2014)
As main tourist attraction in Bogor, Bogor Botanical Garden could play a significant role in contributing to a better environment and appreciation to God’s blessing. This research tries to review the actual assessment of Bogor Botanical Garden performance as tourist attractions using tri hita karana concept and corporate social responsible (CSR) principles. Both tri hita karana concept and CSR principles has similar objective and can complement each other very well. It is concluded that both concepts are applicable and could enhance Bogor Botanical Garden role in promoting better environment and appreciation to God’s blessing. The implementation of tri hita karana has been done in harmony with local wisdom, whilst the CSR is supported by private corporations.